Spontaneous bacterial peritonitis caused by Gram-negative bacteria: an update of epidemiology and antimicrobial treatments. (3rd July 2019) - Fiore, Marco; Di Franco, Sveva; Alfieri, Aniello; Passavanti, Maria Beatrice; Pace, Maria Caterina; Kelly, Molly E.; Damiani, Giovanni; Leone, Sebastiano
ABSTRACT: Introduction : Spontaneous bacterial peritonitis (SBP) is a main infectious complication in end-stage liver disease (ESLD) patients. The increasing trend of bacterial resistance in ESLD patients with SBP has been associated with low treatment efficacy of traditional therapy. Cephalosporin use has been restricted to community-acquired infections and in areas/health care settings with low rates of multidrug-resistant (MDR) bacteria. To date, several changes are necessary with regard to empiric therapy recommendations in areas/health care settings with high rates of MDR bacteria. Areas covered : An overview of the epidemiology and antimicrobial treatments of SBP caused by Gram-negative bacteria. Expert opinion : Broad-spectrum antibiotics have been recommended as empiric therapy for suspected SBP in areas/health care settings with high rates of MDR bacteria and secondary treatment, with newer antibiotics, for SBP caused by MDR-Gram-negative bacteria (i.e. new beta-lactam/beta-lactamase inhibitor combinations, cefiderocol, plazomicin, and eravacycline) either alone or in combination.